2019
DOI: 10.1088/1742-6596/1236/1/012041
|View full text |Cite
|
Sign up to set email alerts
|

On approximation and experimental accuracy in dynamic light scattering

Abstract: The work is dedicated to estimation of accuracy of calculations in dynamic light scattering experiments, in particular approximation and size determination of nanoparticles in polydisperse solutions. In dynamic light scattering the proper approximation is crucial to final accuracy of sizes calculations, especially if we consider polydisperse solutions, such as biological fluids. Calculated and experimental errors have been compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The absorption spectrum of blood serum was studied in [32,33]. The circuit elements selected according to calculated requirements provided signal-to-noise ratio (SNR) of more than 10 for all detected signals [28]. SNR was calculated using [34][35][36].…”
Section: Dynamic Light Scattering Spectrometermentioning
confidence: 99%
See 3 more Smart Citations
“…The absorption spectrum of blood serum was studied in [32,33]. The circuit elements selected according to calculated requirements provided signal-to-noise ratio (SNR) of more than 10 for all detected signals [28]. SNR was calculated using [34][35][36].…”
Section: Dynamic Light Scattering Spectrometermentioning
confidence: 99%
“…In the commercial DLS spectrometers, the maximum number of components correctly resolved by the algorithm does not exceed 3. The testing of the algorithm and the used spectrometer is described in [28]. It was shown that the error in determining the size of structures in a liquid is less than 8%.…”
Section: Dynamic Light Scattering Spectrometermentioning
confidence: 99%
See 2 more Smart Citations